2016
DOI: 10.1111/1475-6773.12404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Health Insurance on Diabetes and Hypertension Process Indicators among Older Adults in Mexico

Abstract: Social health insurance for the poor improved some but not all health care process indicators among diabetic and hypertensive older people in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Three studies evaluated the impact of reducing user charge on chronic condition–related outcomes (with two studies in Mexico and one in Ghana)39 42 43 (online supplementary table 5). Outcomes in these three studies included blood glucose control (HbA1c), adherence to medication, diet and exercise for hypertension and diabetes, and anaemia.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies evaluated the impact of reducing user charge on chronic condition–related outcomes (with two studies in Mexico and one in Ghana)39 42 43 (online supplementary table 5). Outcomes in these three studies included blood glucose control (HbA1c), adherence to medication, diet and exercise for hypertension and diabetes, and anaemia.…”
Section: Resultsmentioning
confidence: 99%
“…The instrumental variable used in the present study (the interaction between the logarithm of population density at the municipality level in year 2000 and a dummy for whether Ensanut was conducted in 2005-6) takes into account the fact that the intensity of the roll-out process and the penetration of SP over the study period were not equally distributed across different areas. As explained in other studies, 6 SP was introduced in 2002 and gradually adopted by all the states by 2005. At first, it was targeted to smaller areas in order to achieve universal coverage more quickly; 18,19 however, after 2006, SP spread to more urbanized areas.…”
Section: Analytic Strategymentioning
confidence: 91%
“…3,4 In contrast, recent studies have found that SP had little to no impact on diabetes and hypertension treatment and care among Mexican elders, and even produced an increase in ambulatory care sensitive hospitalizations (ACSH). 5,6 Effective preventive care for older adults can reduce health care costs and reduce multimorbidity and mortality. 7 SP provides a package of services that is limited in scope and availability since patients need to be treated via the SP network of health facilities.…”
Section: Preventive Healthcare-seeking Behavior Among Poor Older Adulmentioning
confidence: 99%
See 1 more Smart Citation
“…) using cross‐sectional information for several years, combined with other techniques such as instrumental variables or propensity score matching, seems very promising. Applying this approach, Rivera‐Hernandez et al () suggested that older Mexican adults covered by SP have better pharmacologic treatment for diabetes than their noninsured counterparts. However, they found no impact of SP on either pharmacologic treatment for hypertension or nonpharmacologic treatment for either diabetes or hypertension.…”
mentioning
confidence: 99%